1995
DOI: 10.1029/95jd00275
|View full text |Cite
|
Sign up to set email alerts
|

A reanalysis of carbonyl sulfide as a source of stratospheric background sulfur aerosol

Abstract: This study investigates the importance of carbonyl sulfide (OCS) in the formation of stratospheric background sulfur aerosol. Specific questions examined include the loss rate in the stratosphere, the net flux into the stratosphere, and the contribution of OCS to the stratospheric background sulfur aerosol. From an analysis of current atmospheric measurements of OCS, the total amount of OCS in the atmosphere is evaluated to be 5.2 Tg. Of this total, 4.63 Tg is in the troposphere and 0.57 Tg in the stratosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
193
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(213 citation statements)
references
References 51 publications
20
193
0
Order By: Relevance
“…It is very interesting that the maximal yields of CO 2 and H 2 S lagged behind the maximal consumption of COS. This phenomenon is related to the adsorption of CO 2 and H 2 S on the basic site of MgO. In Figure 1, the maximal yield of H 2 S was also later than that of CO 2 , which could be explained by the reasons that the acidity of H 2 S is stronger than that of CO 2 , and thus H 2 S is more readily to be adsorbed on the basic site of MgO.…”
Section: Reaction Pathway and Kinetics For The Heterogeneousmentioning
confidence: 87%
See 2 more Smart Citations
“…It is very interesting that the maximal yields of CO 2 and H 2 S lagged behind the maximal consumption of COS. This phenomenon is related to the adsorption of CO 2 and H 2 S on the basic site of MgO. In Figure 1, the maximal yield of H 2 S was also later than that of CO 2 , which could be explained by the reasons that the acidity of H 2 S is stronger than that of CO 2 , and thus H 2 S is more readily to be adsorbed on the basic site of MgO.…”
Section: Reaction Pathway and Kinetics For The Heterogeneousmentioning
confidence: 87%
“…The vacuum chamber between the QMS and the Knudsen cell reactor was pumped by a 60 L‚s -1 turbomolecular pump for differential pumping of the mass spectrometer and an ion gauge (both from BOC Edward). The Knudsen cell reactor consisted of a stainless steel chamber with a gas inlet controlled by a leak valve, an escape aperture whose area can be adjusted with an adjustable iris in the range of 0-300 mm 2 , and a sample holder attached to the top ceiling of a circulating fluid bath. The effective area of escape aperture was measured in each independent experiment according to the attenuation of the N 2 signal from one steady state to another.…”
Section: Experimental Methods Kcms Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This aerosol layer, referred to as the Junge layer, mainly consists of sulphate aerosol that is chiefly formed by sulphur dioxide (SO 2 ) produced from photo-dissociation of carbonyl sulphide (OCS) transported from the troposphere (Crutzen, 1976). However studies indicate that OCS is not enough to explain the observed aerosol load (Chin and Davis, 1995), and direct transport of SO 2 or sulphate aerosol have been suggested as important contributions to stratospheric aerosol (Pitari et al, 2002;Myhre et al, 2004). Volcanic injections however makes it difficult to determine the background state of the stratospheric aerosol layer (Solomon et al, 2011), and thereby the importance of different sources for its production.…”
mentioning
confidence: 99%
“…1 OCS is relatively unreactive in the troposphere, where it is present at near constant mixing ratios of ∼500 ppt, but concentrations drop off sharply in the stratosphere, as shorter wavelength photolysis becomes increasingly important. 2 As a source of atomic sulfur, photolysis of OCS makes a significant nonvolcanic contribution to the stratospheric sulfate aerosol layer. 3,4 The first absorption band of OCS is responsible for its photochemistry in the stratospheric UV window and has been extensively studied.…”
Section: ■ Introductionmentioning
confidence: 99%